Structures of quaternary chromium silicides revealed by a combination of resonant X-ray diffraction and ab initio calculations. (February 2019) - Brix, Florian; Gaudry, Emilie; François, Michel; Elkaïm, Erik; Desgranges, Clara; Sallot, Pierre; Mathieu, Stéphane; Vilasi, Michel
Abstract: The energetic stability and oxidation behaviour of quaternary chromium silicides mainly depends on their chromium content. In this work, the pseudolamellar crystal structures of six representatives of the X3 T2 (T1-x Crx )2 Si6 compounds (X = Nb or Ti and T = Fe, Co or Ni) are determined by resonant X-ray diffraction using the synchrotron facility, combined with calculations based on the density functional theory. Experimentally, the transition metal positions are determined using the anomalous scattering effect close to the energy absorption threshold. First principles calculations carried out on the as-determined structures show that the preferential site occupations are explained by thermodynamic arguments. Theoretical calculations highlight the influence of Cr atoms on the lattice parameters, and reveal that the experimental Cr content corresponds to the amount required to reach the equilibrium between X3 T2 (T1-x Crx )2 Si6 and X4 T4 Si7 . Highlights: X3 T2 (T1-x Crx )2 Si6 structure was studied with Rietveld refinement on synchrotron X-ray diffraction. Equilibrium Cr composition is in agreement with ab initio calculations highlighting the stabilizing effect of Cr. Both X-ray and calculations showed Cr is preferentially located on one disordered site. Bonding strengths of Cr-Si seem to play a role in this preference.